Labor markets for health supply chain management in Rwanda: a qualitative study of stakeholder perspectives - Erin Meier; Andrew N. Brown; Bridget McHenry; Inès K. Gege Buki; Michael Egharevba; Joseph Kabatende (BMC, 2023)
Abstract Background Effective supply chains for health products require an adequate, skilled workforce for supply chain management (SCM). Rwanda faces challenges in human resources for SCM, including limited capacity for SCM at different levels. Understanding of the factors influencing the supply of and demand for SCM professionals in Rwanda is necessary to ensure the labor market contains an adequate workforce. This study identifies the perspectives of key stakeholders in the supply chain management sector about the factors influencing the supply of and demand for SCM professionals. Methods Data were collected in semi-structured group and one-on-one interviews with 39 key stakeholders involved in the supply chain management labor market between March and April 2019. Interviewees were categorized according to their role in the labor market as system actors, functional actors involved in the supply of SCM workers, and functional actors involved in the demand for SCM workers. Interviewees were asked open-ended questions about factors influencing the demand for and the supply of SCM workers, and recommendations for improvement. Interviews were analyzed thematically. One validation focus group was held and the results were also reviewed by the Ministry of Health in Rwanda. Results Stakeholders agreed that skills mismatch between SCM workers' skills and the competencies jobs require impacts the supply of workers. A lack of career structure for SCM, lack of professional definitions for health supply chain management, and SCM curricula that do not match the needs of the workplace contribute to this gap. The demand for SCM professionals is poorly defined in terms of the numbers of professionals needed and the skills workers require. Financial limitations hinder demand for health SCM professionals. Conclusions This study adds to the understanding of factors influencing the SCM labor market in Rwanda by documenting perspectives from government ministries, professional organizations, universities, and employers from SCM organizations. Improving the SCM labor market in Rwanda and the availability of the skilled cadres required for the effective management of health supply chains in Rwanda requires a coordinated effort by the Ministry of Health in Rwanda, private SCM companies, professional associations, education sector, and policy makers.